In silico phylogenetic analysis of Vibrio cholerae isolates based on three housekeeping genes. (1st January 2015) - Farhadi, Tayebeh; Nezafat, Navid; Ghasemi, Younes
Vibrio cholera, a gram–negative bacterium, has been categorised into clinical and environmental species. Phylogenetic studies have been performed to investigate the relationships of the V. cholerae populations in worldwide. In this study, phylogenetic relationship between V. cholerae isolates from Iran and other regions of the world was determined, based on three housekeeping genes analysis. Results for Iranian strains showed that congruency of asd and hlyA phylogenetic trees were remarkably higher than recA tree. Iranian strains displayed 2-3%, 1-14% and 3-5% deference in asd, hlyA and recA nucleotide sequences, respectively. Sequence similarity degrees were variable between Iranian and other region's strains. Furthermore, the non–congruence in the phylogeny of the pathogenic clones in cladograms is probably due to horizontal gene transfer. Finally, results of this study suggest that monitoring of surface waters for housekeeping genes of V. cholerae in the cholera endemic areas may be valuable for forecasting the expected cholera outbreaks.